Mediatization of Clothing Consumption Among Muslim Teenagers - Hakim, Putri Rahmah Nur; Asyifa, Nahdia; Saputra, Hanif; Adli, Muhammad; Al Fajri, Mirza; Maulina, Winda (IAS Journal of Localities, 2024)
This study aims to explore the impact of media, especially online shop platforms, on Muslim teenagers’ clothing choices by considering religious values and media exposure. This research has a high urgency since it illustrates the impact of mediatization of clothing consumption on Muslim teenagers, who face a dilemma between maintaining religious identity and following fashion trends promoted by the media. in the context of globalization and cultural change, this phenomenon creates serious challenges that need to be understood and addressed by focusing on religious identity and values embraced by individuals, this research fills the gap from previous studies that tend to be underrepresented and geographically limited. Through a qualitative approach, this study examines the clothing consumption characteristics of Muslim teenagers by comparing previous research and journals and analyzing data from interviews and observations. The results highlight online media as a major factor in influencing the selection and consumption of clothing that may not be in line with religious principles. Recommendations for future studies include a broader analysis involving all religions in the digital age, and investigating the factors that influence the selection and consumption of clothing that may not be in line with religious principles.